Light‐Emitting Diodes: Enhanced Brightness and Device Lifetime of Quantum Dot Light‐Emitting Diodes by Atomic Layer Deposition (Adv. Mater. Interfaces 12/2020). Issue 12 (23rd June 2020) - Kim, Gi‐Hwan; Noh, Kyeongchan; Han, Jisu; Kim, Minsu; Oh, Nuri; Lee, Woongkyu; Na, Hyon Bin; Shin, Chansun; Yoon, Tae‐Sik; Lim, Jaehoon; Cho, Seong‐Yong
Abstract : The atomic layer deposited (ALD) ZnO significantly enhances the luminance and device lifetime of green‐emitting quantum dot (QD) light‐emitting diodes. In article number 2000343, Jaehoon Lim, Seong‐Yong Cho, and coworkers show that ALD ZnO provides improved interfacial property with QDs due to the smooth roughness from the ALD growth nature and ligand exchange behavior.